2021
DOI: 10.17344/acsi.2020.6308
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition and Growth of Iron from an Ethylene Glycol Solution

Abstract: The electrochemical reduction of iron (III) ions into zero-valent iron from a solution of ethylene glycol was accomplished. The kinetics and mechanism of the electroreduction process were investigated by cyclic and linear polarization techniques. The influence of temperature, potential sweep rate, and concentration of iron (III) ions on the electroreduction process was also studied. The observed values of effective activation energy revealed that the investigated electroreduction process is accompanied by mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, understanding of kinetic and mechanistic aspects of metal electrodeposition from type-IV DESs is still lacking. Thus, most of works reported in these eutectic systems focused on the bulk electrodeposition of metals [17][18][19][20][21]. Moreover, it has been shown that the behavior of the eutectic system based on EG solutions suffers additional problem called migration effect to the electrode surface during the electrodeposition process, causing difficulties in kinetic studies, which involve diffusional range.…”
Section: Introductionmentioning
confidence: 99%
“…However, understanding of kinetic and mechanistic aspects of metal electrodeposition from type-IV DESs is still lacking. Thus, most of works reported in these eutectic systems focused on the bulk electrodeposition of metals [17][18][19][20][21]. Moreover, it has been shown that the behavior of the eutectic system based on EG solutions suffers additional problem called migration effect to the electrode surface during the electrodeposition process, causing difficulties in kinetic studies, which involve diffusional range.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to emphasize that the properties of such thin metal chalcogenide films can be carefully adjusted and optimized by controlling their thickness, composition and microstructure. This makes it possible to obtain materials with unique properties that can be used to develop new devices and technologies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned water in DESs can be introduced during the storage and electrodeposition process because one of its forming components, choline chloride, is very hygroscopic . To remove the effect of water, several literature studies have proposed simply the sole use of EG as the (non-aqueous) solvent for the electrodeposition of metals. However, the knowledge on aspects such as mechanisms and kinetics of the early stage of Ni electrodeposition from EG solutions onto a glassy carbon electrode (GCE) is still insufficient. Previous works dealing with the nucleation and growth phenomena of metals (Co, Al, Cr, Fe, etc.)…”
Section: Introductionmentioning
confidence: 99%